Existence d'une solution positive pour une équation différentielle fractionnaire - Khadidja Adjailia (My University, 2024)
It is well known that the fixed point theory plays a very important role in solving some mathematical problems, such as the existence of solutions for fractional differential equations...etc. In this memoir, by the fixed point theory for single value mapping, we present some results for the following problem with integrals conditions 〖(_^C)D〗^α u(t) = f( t, u(t)),t∈ [0,1] , ( 1) u(0) = λ∫_0^1▒〖u(s)〗 ds+ 𝒹, ( 2) Where 0<α<,λ ≥0 , 𝒹 ∈ R^+, 〖(_^C)D〗^α is the standard Caputo fractional operator and f:[0,1]× R^+→ R^+is continuous. The technique used to proving these results depends on the upper and lower solution, the Schauder fixed point theorem and the Banach contraction principle. ---------------------------------------------------------------------------------- ومن المعروف ان نظرية النقط الثابتة تلعب دوراً هاماً جداً في الحل لبعض المشاكل الرياضية، على سبيل المثال وجود حلول للمعادلات التفاضل الكسري ... الخ. في هذها المذكرة ، وباستخدام نظرية النقطة الثابتة ، سنقدم بعض النتائج للمشكلة التالية مع شروط التكامل: 〖(_^C)D〗^α u(t)= f( t, u(t)),t∈ [0,1] , ( 1) u(0)=λ∫_0^1▒〖u(s)〗 ds+ 𝒹, ( 2) مستمر f:[0,1]× R^+→ R^+هو عامل الكسر القياسي لكابوتو و 〖(_^C)D〗^α , 𝒹 ∈ R^+, λ ≥0 ,0<α<1 حيث تعتمد التقنية المستخدمة لإثبات هذه النتائج على الحل العلوي والسفلي ونظرية شودر، نظرية النقطة الثابتة ومبدأ الانكماش لباناخ. ------------------------------------------------------------------------------ Il est bien connu que la théorie de point fixe joue un rôle très important dans la résolution de certains problèmes mathématiques par exemple l'existence de solutions pour des équations différentielle fractionnaire ... etc. Dans ce mémoire, par la théorie du point fixe, on va présenter quelques résultats du problème Suivant avec des conditions intégrales: 〖(_^C)D〗^α u(t) = f( t, u(t)),t∈ [0,1] , ( 1) u(0)= λ∫_0^1▒〖u(s)〗 ds + 𝒹, ( 2) Où 0<α<1, λ ≥0 ,𝒹 ∈ R^+ 〖,(_^C)D〗^α est l'opérateur fractionnaire standard de Caputo et f:[0,1]× R^+→ R^+est continuos. La technique utilisée pour prouver ces résultats dépend de la solution supérieure et inférieure, du théorème du point fixe de Schauder et du principe de contraction de Banach.